2013
DOI: 10.1016/j.annepidem.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of cortisol in human hair: implications for epidemiologic studies on health effects of chronic stress

Abstract: Assessment of cortisol concentrations in hair is one of the latest innovations for measuring long-term cortisol exposure. We performed a systematic review of correlates of cortisol in human hair to inform the design, analysis and interpretation of future epidemiologic studies. Relevant publications were identified through electronic searches on PubMed, WorldCat, and Web of Science using keywords, “cortisol” “hair” “confounders” “chronic” “stress” and “correlates.” Thirty-nine studies were included in this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
166
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(179 citation statements)
references
References 103 publications
(213 reference statements)
9
166
2
2
Order By: Relevance
“…The small sample size, primarily composed of females of moderate-to-high socioeconomic status may, however, have restricted the statistical power to detect these effects. Mixed findings have also been found in regards to BMI and cigarette, alcohol and drug consumption, although the available data are insufficient to draw meaningful conclusions at this point in time (Wosu et al, 2013; although see Rippe et al, 2016). The investigation further contributes to existing research aiming to identify the hair cortisol's potential confounders.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…The small sample size, primarily composed of females of moderate-to-high socioeconomic status may, however, have restricted the statistical power to detect these effects. Mixed findings have also been found in regards to BMI and cigarette, alcohol and drug consumption, although the available data are insufficient to draw meaningful conclusions at this point in time (Wosu et al, 2013; although see Rippe et al, 2016). The investigation further contributes to existing research aiming to identify the hair cortisol's potential confounders.…”
Section: Discussionmentioning
confidence: 86%
“…Blood collection is invasive, may inadvertently increase the measurement of acute cortisol secretion, requires trained research assistants (Wosu et al, 2013) and both blood and saliva require storage equipment (e.g. freezers).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence is accumulating for the potential application of HCC in clinical and epidemiological studies (Wester and van Rossum, 2015;Wosu et al, 2013) and various relationships have been demonstrated between HCC and, for example, Cushing's Syndrome (Manenschijn et al, 2012), cardiovascular disease (Manenschijn et al, 2013), depression and mood disorders (Dettenborn et al, 2012b), and anxiety (Steudte et al, 2011). However, the association between HCC and subjectively measured stress remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Additional confounding may be present with the analysis of older hair segments. While the majority of studies have not found an association with the frequency of hair washing, some have reported declining hair cortisol in older hair segments (22). This may be in part due to repeated shampooing as found by Hamel et al (23).…”
Section: Resultsmentioning
confidence: 83%